Pengaruh Visual Brand Communication dan Kualitas Produk terhadap Brand Experience : Survei pada Konsumen Kosmetik Wardah di Kota Tasikmalaya - Denthanika Shena Bagia; Ari Arisman; Barin Barlian (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine the effect of Visual Brand Communication and Product Quality on Brand Experience (Survey of Wardah Cosmetics Consumers in Tasikmalaya City). The method used in this study is causality through a survey approach. With a research sample of 100 Wardah Cosmetic Consumers in Tasikmalaya City. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed that Visual brand communication has very good assessment criteria, product quality has very good assessment criteria and brand experience has good rating classifications. Visual brand communication and product quality simultaneously have a significant effect on brand experience, meaning that they are able to improve brand experience together. Partially, Visual Brand Communication has a significant influence on Brand Experience. Partially Product Quality has a significant effect on Brand Experience, meaning that both variables are proven to improve brand experience.